Effect of impact energy on the impact-wear properties of low carbon high manganese alloy steels in corrosive conditions - Wang, Kai; Du, Xiao-Dong; Youn, Kuk-Tae; Hayashi, Yasunori; Lee, Chan Gyu; Koo, Bon Heun (Metals and materials international, 2008)
The impact-wear properties of low carbon high manganese alloy steel were tested under three different impact energies (0.7 J, 1.2 J and 1.7 J) using a modified MLD-10 wear tester. SEM inspection of the wear surface and subsurface optical metallographic analysis reveal the impact wear mechanism. Under corrosive conditions we observe a shift from single micro-cutting to impact-flaking, after the appearance of vertical section micro-cracks, while at higher impact energies fatigue corrosion and abrasion are observed.